Arthroscopic shoulder surgery in female professional tennis players: Ability and timing to return to play - Young, S. W.; Dakic, J.; Stroia, K.; Nguyen, M. L.; Safran, M. R. (Clinical Journal of Sport Medicine, 2017)
Objective: To assess the outcome and time to return to previous level of competitive play after shoulder surgery in professional tennis players. Design: Retrospective case series. Setting: Tertiary academic centre. Patients and Interventions: The records of all female tennis players on the Women's Tennis Association (WTA) professional circuit between January 2008 and June 2010 were reviewed to identify players who underwent shoulder surgery on their dominant (serving) shoulder. Main Outcome Measures: Primary outcomes were the ability and time to return to professional play and if they were able to return to their previous level of function as determined by singles ranking. Preoperative and postoperative singles rankings were used to determine rate and completeness of return to preoperative function. Results: During the study period, 8 professional women tennis players from the WTA tour underwent shoulder surgery on their dominant arm. indications included rotator cuff debridement or repair, labral reconstruction for instability or superior labral anterior posterior lesion, and neurolysis of the suprascapular nerve. seven players (88%) returned to professional play. The mean time to return to play was 7 months after surgery. However, only 25% (2 of 8) players achieved their preinjury singles rank or better by 18 months postoperatively. In total, 4 players returned to their preinjury singles ranking, with their peak singles ranking being attained at a mean of 2.4 years postoperatively. Conclusions: in professional female tennis players, a high return to play rate after arthroscopic shoulder surgery is associated with a prolonged and often incomplete return to previous level of performance. Thus, counseling the patient to this fact is important to manage expectations. Level Of Evidence: Level IV--Case Series. ABSTRACT FROM AUTHOR